Simultaneous analysis of 29 synthetic cannabinoids and metabolites, amphetamines, and cannabinoids in human whole blood by liquid chromatography–tandem mass spectrometry – A New Zealand perspective of use in 2018. Issue 2 (28th November 2019) - Ong, Rui Shen; Kappatos, Diana C.; Russell, Sarah G.G.; Poulsen, Helen A.; Banister, Samuel D.; Gerona, Roy R.; Glass, Michelle; Johnson, Cameron S.; McCarthy, Mary‐Jane
Abstract: We describe the validation of a method for the simultaneous analysis of 29 synthetic cannabinoids (SCs) and metabolites, 4 amphetamines, and 2 cannabinoids in human whole blood. This method enables one analysis to cover what previously required multiple analyses for these classic and novel drugs‐of‐abuse with diverse physicochemical properties. The scope of targeted analytes was based on the most prevalent drugs‐of‐abuse and SCs encountered at the New Zealand border in 2017 and included parent compounds and metabolites belonging to the indole and indazole carboxamide, quinolinyl indole carboxylate, and naphthoylindole classifications. Samples were prepared by supported‐liquid‐extraction (SLE) followed by liquid chromatography−tandem mass spectrometry (LC−MS/MS) analysis with positive electrospray ionization (ESI). The method was validated with respect to selectivity, matrix effects, process efficiency, sensitivity, repeatability, extract stability, and carryover for qualitative confirmation. Linearity as well as accuracy and precision data at target decision concentrations were also evaluated. The limits of detection and confirmation ranged from 0.1 to 6.0 ng/mL and 1.0 to 6.0 ng/mL, respectively. The described method was successfully applied to the analysis of 564 ante‐ and post‐mortem blood samples in 2018. There were 132 cases (23%) with positive findings of at least one SC, with the five most commonly detected SCs being AMB‐FUBINACA and/or acid (61%), 5F‐ADB and/or acid (40%), ADB‐FUBINACA (11%), 5F‐MDMB‐PICA acid (6%), and MDMB‐FUBINACA acid (6%). The results also demonstrate the predominant presence of metabolites at higher levels than the unchanged parent SCs in blood, highlighting the need to maintain forensic screening methods capable of the simultaneous detection of both parent compounds and metabolites. Abstract : A validated liquid chromatography−tandem mass spectrometry method for the analysis of synthetic cannabinoids and metabolites, amphetamines and cannabinoids in blood is described. The applicability of the method was demonstrated with 132 positive forensic cases in New Zealand in 2018. AMB‐FUBINACA and/or acid (61%), 5F‐ADB and/or acid (40%), ADB‐FUBINACA (11%), 5F‐MDMB‐PICA acid (6%), and MDMB‐FUBINACA acid (6%) were most frequently detected. Semi‐quantitative results showed the predominant presence of metabolites at more amenable levels than the parent synthetic cannabinoids in blood.